O ensino das leis da reflexão e refração da luz na Educação de Jovens e Adultos: uma sequência didática de ensino fundamentada na abordagem de Paulo Freire - SOUSA, José Ribamar de (2024)
This dissertation seeks to explore an innovative pedagogical approach in teaching Physics geared towards Adult and Youth Education (AYE). Drawing upon the principles of emancipatory education outlined by Paulo Freire, which emphasize dialogue and the transformation of naive curiosity into epistemological curiosity, in addition to being grounded in the three pedagogical moments proposed by Demétrio Delizoicov, the research proposes and implements a didactic sequence focused on teaching concepts of geometric optics. The main objective is to engage students and promote learning.The pedagogical proposal stems from Freire's understanding that education is not merely about the transmission of content, but rather empowers students to critically interpret the world around them and transform their reality. The didactic sequence is meticulously planned, encompassing various stages from initial problematization to the practical application of knowledge acquired by students. The central role of experimentation is highlighted, allowing students to actively participate in knowledge construction. The study also incorporates the analysis of pre-surveys, conducting experiments, and organizing a science fair, providing a comprehensive view of the effectiveness of the proposed approach. Results reveal that the methodology was well-received by AYE students, fostering a deeper understanding of optical phenomena. Furthermore, the collaborative and dialogic approach stimulated knowledge sharing and collective knowledge building. The conclusion underscores the importance of this innovative methodology not only for Physics education but also for the development of social and cultural skills. Thus, the research contributes to a more inclusive and transformative education, aligned with Paulo Freire's ideals and aiming to empower students not only as passive recipients of information but as active agents of change in their communities and society at large.